Stoichiometric silicon oxynitride thin films reactively sputtered in Ar/N2O plasmas by HiPIMS. (1st March 2016) - Hänninen, Tuomas; Schmidt, Susann; Wissting, Jonas; Jensen, Jens; Hultman, Lars; Högberg, Hans
Abstract: Silicon oxynitride (SiO x N y, –0.7) thin films were synthesized by reactive high power impulse magnetron sputtering from a pure silicon target in Ar/N2 O atmospheres. It was found that the composition of the material can be controlled by the reactive gas flow and the average target power. X-ray photoelectron spectroscopy (XPS) shows that high average powers result in more silicon-rich films, while lower target powers yield silicon-oxide-like material due to more pronounced target poisoning. The amount of nitrogen in the films can be controlled by the percentage of nitrous oxide in the working gas. The nitrogen content remains at a constant level while the target is operated in the transition region between metallic and poisoned target surface conditions. The extent of target poisoning is gauged by the changes in peak target current under the different deposition conditions. XPS also shows that varying concentrations and ratios of oxygen and nitrogen in the films result in film chemical bonding structures ranging from silicon-rich to stoichiometric silicon oxynitrides having no observable Si–Si bond contributions. Spectroscopic ellipsometry shows that the film optical properties depend on the amount and ratio of oxygen and nitrogen in the compound, with film refractive indices measured at 633 nm ranging between those of SiO2 and Si3 N4 .